Examination of the Quality of Interactions as Observed in Childcare Centers and Reported by Early Childhood Educators. (June 2020) - Duval, Stéphanie; Bouchard, Caroline; Lemay, Lise; Cantin, Gilles
This study aimed to describe the quality of interactions between early childhood educators (ECEs) and children, as observed in childcare centers and as reported by early childhood educators ( N = 15) working with 5 year-old children. To assess ECEs' practices related to the quality of these interactions as observed in childcare centers (theories-in-use), the Classroom Assessment Scoring System (CLASS) was used. This tool is structured around three domains: emotional support, group organization, and instructional support . Semi-structured interviews were conducted with ECEs to collect data on their reported practices related to the quality of these interactions (espoused theories). The observational data showed that the quality of emotional support and group organization was average-to-high, and these domains were also most often referred to in the participants' comments. On the contrary, the quality of instructional support was rated average-to-low. Correspondingly, this domain was not often referred to in the participants' comments. These results are discussed in light of the tensions and gaps brought out between the ECEs' theories-in-use and espoused theories and lead to recommendations for professional development aimed at improving the quality of ECE–child interactions in childcare centers and, in particular, the instructional support provided therein.